2017
DOI: 10.15585/mmwr.ss6607a1
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Health Care Access and Health Services Use, Adults Aged 1864 Years — Behavioral Risk Factor Surveillance System, United States, 2014

Abstract: Problem/ConditionAs a result of the 2010 Patient Protection and Affordable Care Act, millions of U.S. adults attained health insurance coverage. However, millions of adults remain uninsured or underinsured. Compared with adults without barriers to health care, adults who lack health insurance coverage, have coverage gaps, or skip or delay care because of limited personal finances might face increased risk for poor physical and mental health and premature mortality.Period Covered2014.Description of SystemThe Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 30 publications
9
68
1
Order By: Relevance
“…Similar to previous research ( 8 , 9 ), this analysis identified disability-specific disparities in health care access, particularly among young and middle-aged adults. Disability-specific factors, such as severity of disability, age at disability onset, or having multiple disability types or comorbidities might partially explain why persons in these age groups, and those reporting self-care and mobility disabilities, had higher prevalences of access to care than did those reporting vision and hearing disabilities ( 5 , 9 ).…”
Section: Discussionsupporting
confidence: 59%
“…Similar to previous research ( 8 , 9 ), this analysis identified disability-specific disparities in health care access, particularly among young and middle-aged adults. Disability-specific factors, such as severity of disability, age at disability onset, or having multiple disability types or comorbidities might partially explain why persons in these age groups, and those reporting self-care and mobility disabilities, had higher prevalences of access to care than did those reporting vision and hearing disabilities ( 5 , 9 ).…”
Section: Discussionsupporting
confidence: 59%
“…As states participating in BRFSS changed over this period and adoption of the Medicaid expansion varied by state, the impact of changes in the healthcare coverage system on health metrics among this low‐wage workforce could not be evaluated in these analyses. Some research has shown improved healthcare access and some health metrics following the implementation of the ACA, particularly in states that expanded Medicaid . However, the results of other studies highlight residual inequities in access to care due to structural issues ranging from the reluctance of some providers to accept Medicaid patients and inability to afford coinsurance, particularly among the working poor, to lack of transportation, childcare, and employer‐provided time off for preventive care visits .…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the median wage for this workforce was $12.31 per hour . Wages affect healthcare access both directly and through healthcare insurance coverage …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, to address financial barriers to mammography, policy‐based solutions may improve screening rates. For example, studies have shown that cancer screening rates among low‐income individuals were higher in states that expanded Medicaid compared to those that did not, and states that did not expand Medicaid, especially in the South, had higher breast cancer mortality‐to‐incidence ratios and lower screening rates . Because the Affordable Care Act's Medicaid expansion criteria broaden the income level eligibility, expansion may be particularly beneficial for people in the Delta Region, who experience significant economic challenges.…”
Section: Discussionmentioning
confidence: 99%